2019
DOI: 10.1084/jem.20182192
|View full text |Cite
|
Sign up to set email alerts
|

STING-mediated disruption of calcium homeostasis chronically activates ER stress and primes T cell death

Abstract: STING gain-of-function mutations cause lung disease and T cell cytopenia through unknown mechanisms. Here, we found that these mutants induce chronic activation of ER stress and unfolded protein response (UPR), leading to T cell death by apoptosis in the StingN153S/+ mouse and in human T cells. Mechanistically, STING-N154S disrupts calcium homeostasis in T cells, thus intrinsically primes T cells to become hyperresponsive to T cell receptor signaling–induced ER stress and the UPR, leading to cell death. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
214
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(226 citation statements)
references
References 32 publications
(49 reference statements)
12
214
0
Order By: Relevance
“…Stimulator of interferon genes activation on the ER also triggers an ER stress response with an "unfolded protein response (UPR) motif " on the C-terminus of STING, which leads to and ER stress-mediated autophagy (82,83). STING-TBK1 activation and ER stress also induce mechanistic target of rapamycin complex 1 (mTORC1) dysfunction (84).…”
Section: Sting Downstream Signaling Promotes Ifnα/β Expression and Aumentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulator of interferon genes activation on the ER also triggers an ER stress response with an "unfolded protein response (UPR) motif " on the C-terminus of STING, which leads to and ER stress-mediated autophagy (82,83). STING-TBK1 activation and ER stress also induce mechanistic target of rapamycin complex 1 (mTORC1) dysfunction (84).…”
Section: Sting Downstream Signaling Promotes Ifnα/β Expression and Aumentioning
confidence: 99%
“…Localization of STING at the Golgi can cause delay of T-cell mitosis and reduced proliferation independently of IRF3 and TBK1 (215). Furthermore, a "UPR motif " on the C-terminus of STING can cause ER stress and UPR, resulting in Ca 2+ overloading and T-cell death (82). A controversial view is that B cells express STING variously and may undergo apoptosis through this way (166,216,217).…”
Section: Cgas-sting Pathway In Autoimmune or Inflammatory Diseasesmentioning
confidence: 99%
“…Besides, STING activates ER stress and the unfolded protein response (UPR) through a novel motif termed as "the UPR motif", which is located in the helix aa322-343. Long-lasting STINGmediated ER stress and disruption of calcium homeostasis primes T cell death by apoptosis [132][133][134] (Fig.6e).…”
Section: Othersmentioning
confidence: 99%
“…In this study, our data indicated that STING/TBK pathway was activated in the spinal cord of neuropathic pain model. Activated STING signaling triggers ER stress (48). STING-containing endoplasmic reticulum-Golgi intermediate compartment (ERGIC) served as a membrane source for the lipidation of LC3 (20,49,50).…”
Section: Discussionmentioning
confidence: 99%